79 PREOPERATIVE TOBACCO CESSATION AND MAJOR POSTOPERATIVE MORBIDITY IN PATIENTS UNDERGOING ESOPHAGECTOMY. (14th September 2020) - Corsini, E; Mitchell, K; Zhou, N; Antonoff, M; Mehran, R; Rice, D; Roth, J; Sepesi, B; Swisher, S; Vaporciyan, A; Walsh, G; Karam-Hage, M; et al.
Abstract: : While preoperative tobacco cessation has been associated with decreased pulmonary complications in lung cancer patients in the postoperative period, this relationship has not been explored among patients undergoing esophagectomy in this era of increasingly prevalent tobacco cessation campaigns and enhanced recovery after surgery. Methods: We reviewed ever-smokers who underwent esophagectomy at a single institution from January 2004 through June 2019 for esophageal cancer. Occurrence of Clavien-Dindo classification ≥3 major postoperative morbidity (MPM), including anastomotic leak, chylothorax, reoperation, organ dysfunction, respiratory failure, and ICU readmission was calculated. In an effort to evaluate an effect of smoking cessation on outcome, never-smokers were excluded from analyses. Multivariable logistic regression with backwards stepwise elimination was completed to determine the optimal cessation interval associated with reduction in MPM. Robust standard errors were used to account for clustering among surgeons. Results: 725 patients met inclusion criteria, including 666 (92%) with adenocarcinoma and a smaller proportion with squamous cell carcinoma. Most patients were male (650, 90%), and the median age was 63 years (IQR 57–69). Records showed that 505 patients (60%) had quit >5 years prior to esophagectomy, and 82 (11%) were current smokers or had quit within the month preceding esophagectomy. MPM occurred in 213 (29%). After univariate regression, age, gender, pack-year history, operative duration, and FEV1 were included in a multivariable model. While age remained associated wtih MPM, preoperative tobacco cessation of any interval was not associated with outcomes. Conclusion: Our previous publication showed increased complication risk for smokers undergoing esophagectomy compared to non-smokers. However, among ever-smokers, no specific interval of preoperative cessation demonstrated decreased MPM. In a setting of active tobacco cessation programs, patients who have not completely achieved abstinence may still be offered surgery with equivalent perioperative outcomes.